Peran Developer Melalui PPJB Ditinjau dari Asas Proporsionalitas dalam UU Perlindungan Konsumen dan Perumahan - Jovanka Yves Modiano; Ariyanto Hermawan; Victor Imanuel W. Nalle (SAPIENTIA ET VIRTUS, 2026)
Contract law exists as a preventive and repressive measure for conflicts of interest arising from an agreement. In the sale and purchase of property, the agreement is generally set out in a Perjanjian Pengikatan Jual Beli (PPJB, or sale-purchase binding agreement). PPJB generally takes the form of a pre-filled document unilaterally prepared by the developer, making it prone to being categorized as a standard clause prohibited under Law No. 8 of 1999 on Consumer Protection. As an authentic deed made before a notary, PPJB has perfect evidentiary power, but it cannot be used as proof of ownership, so it does not guarantee the consumer's ownership of the agreement's object. From this background, two problem formulations were examined: (1) how is legal protection provided to consumers who have signed or approved a PPJB, and (2) whether pre-filled clauses in a PPJB constitute standard clauses detrimental to consumers. This article uses normative legal research with a statutory approach, analyzes Banten High Court Decision No. 114/PDT/2019/PT BTN as a case study, and processes data using a qualitative descriptive method. The findings show that although a PPJB has perfect evidentiary power in court, it cannot guarantee consumer ownership of the object if a dispute arises during the term of the agreement. Clauses unilaterally drafted by the developer often contain standard clauses detrimental to consumers and, applying the principle of proportionality, are void by operation of law under Article 18 of Law No. 8 of 1999. The developer's responsibility for balancing the parties' bargaining position is therefore central to ensuring that a PPJB is legally and morally valid.